Historical Review of Sino-India Relation: The Fact Sheet on India – China Relations - Oberoi, Pawan Kumar; Kumar, Tanuj (Journal of Commerce and Trade, 2007)
Sino-Indian relations are based on the five principles (Panchsheel) of peaceful co-existence. How this relationship will evolve as we enter the twenty first century, especially when China formally becomes the 143rd member of the World Trade Organization (WTO) is a strategic decision made by the Chinese Government, under the conditions of economic globalization. Marking the new stage of China’s opening up this is an issue that has serious policy implication for India. It is possible that, given its size and growing economy, China mat become India’s major export market but it is also possible that, with its ambition to rapidly catch-up with the advanced economy of the world, China may soon challenge India’s supremacy in technology and know how and become a rival instead of a partner. China has emerged as one of the Asia’s most dynamic newly industrializing economies. In the decade following the reform China’s real GNP grew at an annual average rate of 10 percent, up from and annual rate of 6.5 percent during 1970s. Although its economy slowed in the late 1980s due to the government anti-inflationary measures, it regained momentum in the early 1990s, achieving a 13.4 percent rate of growth in 1993. china’s economy posted somewhat lower growth rate in subsequent year (nearly 12 percent) but not less that 7.8 percent even in the Asian crisis year of 1998.